Satellite monitoring of the Kamchatkan active volcanoes - Girina O.A.; Melnikov D.V.; Manevich A.G.; Nuzhdaev A.A. (Dalnauka, 2014)
Satellite monitoring is one of the most informative methods of monitoring volcanic activity in Kamchatka, as only 10 active volcanoes from 30, have seismic stations. Over the period of more than 20 years polar-orbiting satellites NOAA (AVHRR) have been providing data necessary for on-line monitoring of volcanic activity (tracking of thermal anomalies over volcanoes and ash plumes from explosive eruptions). Advances of remote sensing methods allow recent 24/7 satellite monitoring of active volcanoes. This helps to detect a thermal anomaly over any active volcano and track its growth and temperature in time. Experience of daily satellite monitoring of active Kamchatka volcanoes for the last 12 years and knowledge on peculiarities of their eruptions allows predicting strong explosive eruptions (for example, KVERT predicted 10 strong eruptions of Bezymianny volcano in 2002-2012). The complex analysis of the published data on volcanic activity and the data from 20 years of KVERT continuous monitoring of volcanoes allows to reliably evaluate hazard posed by volcanoes to aviation and population community. Спутниковый мониторинг является одним из наиболее информативных методов слежения за вулканической активностью на Камчатке, так как только на 10-ти действующих вулканах из 30-ти имеются сейсмические станции. На протяжении более двадцати лет основным источником информации для оперативного мониторинга вулканической активности (отслеживания термальных аномалий на вулканах и пепловых шлейфов при их эксплозивных извержениях) во всем мире являются данные полярно-орбитальных спутников серии NOAA (AVHRR). Развитие дистанционных методов наблюдений позволяет в настоящее время проводить непрерывный спутниковый мониторинг действующих вулканов. Это дает возможность зафиксировать появление термальной аномалии в районе каждого активного вулкана, а также проследить рост ее размера и температуры во времени. Опыт ежедневного спутникового мониторинга действующих вулканов Камчатки в течение 10 лет, в совокупности со знаниями особенностей их эруптивной активности, позволяет предсказывать сильные эксплозивные извержения (например, в 2002-2012 гг. группа KVERT предсказала 10 сильных извержений вулкана Безымянный). Многосторонний анализ имеющихся опубликованных сведений о деятельности вулканов, а также данных, полученных сотрудниками KVERT в течение 20-летнего непрерывного мониторинга вулканов, позволяет с большой надежностью оценивать степень вулканической опасности для авиаполетов и населения Камчатки.
Keywords: 38.37.25 Вулканология; Вулканы Камчатки